GAMBARAN KLINIS KANKER PROSTAT DAN BENIGN PROSTAT HYPERPLASIA (BPH) PADA PASIEN RETENSI URIN DI RSUD DR. H ABDUL MOELOEK – BANDAR LAMPUNG TAHUN 2015 - Andi Siswandi; Nita Sahara (Jurnal Ilmu Kedokteran dan Kesehatan, 2019)
Prostate cancer and benign prostate hyperplasia (BPH) include in world health problemsdue to incidence and mortality. Urine retention is symptom of. Clinical overview ofprostate cancer and benign prostate hyperplasia is needed to identify causes of urineretention. The objective of the study was to know the clinical overview of prostate cancerand benign prostate hyperplasia at Dr. H. Abdul Moeloek General Hospital of BandarLampung in 2014.This was a descriptive study done on patients of prostate cancer and benign prostatehyperplasia at Dr. H. Abdul Moeloek General Hospital of Bandar Lampung in 2014.There were 162 respondents consisting 156 (96.3%) BPH cases and 6 (3.7%) prostatecancer. Urine retention was found on either BPH or prostate cancer. The findingrevealed that 60 to 69 year age group had the highest incidences, 3 cases (66.6%), whichclinical overviews were straining (100%), low urine flow (50%), intermittency (66.7%),unreleased (50%), nocturia (66.7%), urgency (50%) and hematuria (66.7%). On theother side, BPH patients in 60 to 69 age group were amounting to 55 cases (35.2%)which clinical overviews were straining (70.5%), low flow urine (64.1%), intermittency(60.9%), unreleased (55.1%), nocturia (57%), urgency (55.8%) and hematuria (50.7%).